Digital Platforms: Legal And Economic Challenges (University of Maribor Press, 2024)
Digital platforms are deeply involved in various social activities, which is why they have become the center of debate on many legal issues related to their operation. The publication addresses a number of legal and economic challenges faced by stakeholders in the digital market, paying special attention to the largest digital platforms or their operators, i.e. digital gatekeepers. It deals with the concept of gatekeepers and interoperability requirements under the Digital Markets Act and the wider legal and economic implications of this, the position of large language models and services related to generative artificial intelligence, and the impact of digital platforms on education. It further analyzes the shortcomings of the management of competition protection policy in digital markets from a legal, management and information point of view and discusses the privacy paradox regarding the balance between digital convenience and the protection of the right to privacy. Special emphasis is also given to challenges in the field of intellectual property law, where their responsibility for copyright and trademark violations is highlighted.